Nutrient intakes of rural Tibetan mothers: a cross-sectional survey - Yan Hong; Dang Shaonong; Wang Zhenjie (BMC, 2010)
Abstract Background Tibetan food intake is influenced by the region's high altitude and unique culture. Few published studies of nutrient intakes among Tibetan women are available. The present study of Tibetan mothers with young children explores dietary patterns, nutrient intakes, and differences between socio-demographic groups. Methods A cross-sectional survey of 386 women with a child aged less than 24 months was conducted in rural areas surrounding Lhasa, Tibet. All participants were recruited using simple random sampling and were interviewed face-to-face by trained investigators. Dietary information was collected via a food frequency questionnaire. Nutrient intakes were calculated using food composition tables. Non-parametric tests were used to compare nutrient intakes according to socio-demographic variables, and to compare results with the 2002 Chinese National Nutrition and Health Survey (2002 NNHS) and dietary reference intakes (DRIs). Results Median intakes of energy (p < 0.001), protein (p < 0.001), fat (p < 0.001), vitamin A (p < 0.001), vitamin B1 (p < 0.001), vitamin B2 (p < 0.001), vitamin C (p < 0.001), and vitamin E (p < 0.001) were lower than the average levels reported in 2002 NNHS. The median intakes of calcium (517 mg/d, p < 0.001), iron (35 mg/d, p < 0.001), and zinc (17.3 mg/d, p < 0.001) were higher than the average levels in 2002 NNHS. The highest education subgroup had significantly higher intakes of vitamins A and C than the lowest education subgroup. Conclusion Although the diet of Tibetan mothers with young children has been partially influenced by other factors, their dietary patterns are still mostly composed of Tibetan traditional foods. Compared with the 2002 NNHS, Tibetan women with young children appear to have insufficient intakes of many nutrients, which will affect their nutritional status.